Python crash course : a hands-on, project-based introduction to programming - Matthes, Eric, ....- (USA : William Pollock, 2019)
Second edition of the best-selling Python book in the world. A fast-paced, no-nonsense guide to programming in Python. Updated and thoroughly revised to reflect the latest in Python code and practices. Python Crash Course is the worlds best-selling guide to the Python programming language. This fast-paced, thorough introduction to programming with Python will have you writing programs, solving problems, and making things that work in no time. In the first half of the book, youll learn basic programming concepts, such as variables, lists, classes, and loops, and practice writing clean code with exercises for each topic. Youll also learn how to make your programs interactive and test your code safely before adding it to a project. In the second half, youll put your new knowledge into practice with three substantial projects: a Space Invaders-inspired arcade game, a set of data visualizations with Pythons handy libraries, and a simple web app you can deploy online. As you work through the book, youll learn how to:bUse powerful Python libraries and tools, including Pygame, Matplotlib, Plotly, and DjangobMake 2D games that respond to keypresses and mouse clicks, and that increase in difficultybUse data to generate interactive visualizationsbCreate and customize web apps and deploy them safely onlinebDeal with mistakes and errors so you can solve your own programming problemsIf youve been thinking about digging into programming, Python Crash Course will get you writing real programs fast. Why wait any longer? Start your engines and code!
Includes index.
Description based on online resource; title from title page (Safari, viewed June 4, 2019).
Keywords: Electronic books; Python (Computer program language).; programming